2020
DOI: 10.3389/fpsyt.2020.00516
|View full text |Cite
|
Sign up to set email alerts
|

Affective Switch Associated With Oral, Low Dose Ketamine Treatment in a Patient With Treatment Resistant Bipolar I Depression. Case Report and Literature Review

Abstract: There is a growing evidence for the rapid and robust antidepressive effect of ketamine in unipolar and bipolar treatment resistant depression although evidence for the risk of affective switch is still limited. This case presents bipolar I disorder patient with treatment resistant depressive episode experiencing a switch to manic episode with mixed features shortly after receiving eight subanaesthetic doses of oral ketamine as an add-on treatment preceded by 2-day period of manic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although the risk of an affective switch in available studies seems low, manic symptoms should be monitored in bipolar patients treated with ketamine, especially those treated with antidepressants. 50 In this study, no affective switch was observed, although more studies on larger groups of bipolar patients are needed to confirm this observation.…”
Section: Discussionmentioning
confidence: 49%
“…Although the risk of an affective switch in available studies seems low, manic symptoms should be monitored in bipolar patients treated with ketamine, especially those treated with antidepressants. 50 In this study, no affective switch was observed, although more studies on larger groups of bipolar patients are needed to confirm this observation.…”
Section: Discussionmentioning
confidence: 49%
“…Figure 3 and Table 4 demonstrate no significant changes in YMRS scores during ketamine therapy, suggesting that none of our patients exhibited an affective switch. Data on affective switch during ketamine therapy in the literature are limited and inconsistent, necessitating further investigation ( Niciu et al, 2013 ; Allen et al, 2019 ; Wilkowska et al, 2020 ). We observed a decrease in dissociative symptoms in both groups ( Figures 4 , 5 and Tables 5 , 6 ), as measured by CADSS before and 30 min after infusion.…”
Section: Resultsmentioning
confidence: 99%
“…One risk associated with the antidepressant use of psychotomimetic drugs, sleep deprivation, fasting or ketogenic diet is the possibility of triggering a switch towards mania and psychosis. 204 , 205 , 206 There are plenty of examples, however, when compensatory switches—even ones that resemble mania or psychosis—do not lead to progressive dysregulation and dysfunction. The transition from initial shamanic sickness to shamanic death‐rebirth experience and shamanic election 207 is one example, as are innumerable other types of salvific, spiritual or secular self‐transformative experiences.…”
Section: Classic Psychedelic Compensation: 5‐ht2ar Activationmentioning
confidence: 99%